Baja calidad del servicio en atención al cliente en los hoteles de tres estrellas de los distritos de Tarapoto y la Banda de Shilcayo - Ramirez Muñoz, Sandra Elizabet (2016)
The following research aimed to know the quality level in the customer service that the three-star hotels of Tarapoto and Banda de Shilcayo's district offer; in which it has used surveys and interviews direct to collaborators and professionals involved in the field. This research justifies why the hotel companies are forced to adapt the requirements demanded by its customers as changes occur over time. For that, the first step should be to know very well the current situations that are facing these companies. The research aim was to determine the quality or satisfaction of customer service at the three-star hotels of Tarapoto and Banda de Shilcayo's district. Taking into account variables like: organizational climate, internal communication and training as it is set out in our hypothesis as the main causes. The obtained results of the surveys and interviews show that the organizational climate and the few training are the main causes of the low quality of customer service at these hotels; internal communication in a lower percentage also has its contribution to these results. In conclusion we can say that the three-star hotels in Tarapoto and Banda de Shilcayo show low quality for having mainly an inadequate organizational climate and a weak training with its collaborators. The results of this research contribute to all persons and companies interested in providing good customer service in the field of three-star hotels